SpendSplit / Wan Musyirah Wan Ismail ... [et al.] - Wan Ismail, Wan Musyirah; Mazariwan, Iman Alia Nafisah; Abdullah, Muhammad Zulfikar; Hasanuddin, Muhammad Hareez; Mohd Radzi, Anwar Ibrahim (Universiti Teknologi MARA, Kedah, 2023)
Introducing SpendSplit, it is an extensive financial website that divides your finances into three main categories: investments, savings, and spending. It gives you a comprehensive picture of your financial situation through thorough analysis and tracking, enabling you to take well-informed decisions and successfully reach your financial objectives. Individuals who do not organize their finances often encounter difficulties and failures. People frequently suffer with growing debt, insufficient savings for emergencies or retirement, bad investment choices, and trouble attaining their long-term financial objectives in the absence of a sound financial plan. This emphasizes the critical importance of sound financial planning in ensuring stability and success. The "SpendSplit" website's goal is to give consumers a thorough platform for effectively planning their money. The website seeks to assist users in gaining insight, making educated decisions, and achieving their financial objectives with more control and organization by segmenting financial information into three important categories: saving, expenses, and investments. SpendSplit distinguishes itself from other financial websites by taking a novel approach to simplifying financial planning. It has an easy-to-use interface that divides down financial data into important categories such as savings, spending, and investments. SpendSplit, with its straight-forward features, personalized insights, and actionable suggestions, offers a complete and user-centric solution for individuals to efficiently manage their money. SpendSplit improves financial literacy and enables people to make more educated decisions. It promotes effective money management, better financial decisions, and progress towards financial objectives by offering a comprehensive perspective of savings, expenditures, and investments, resulting in enhanced financial well-being and community stability. SpendSplit caters to people of all ages, assisting them in properly managing their spending. While engagement with banking industries is not required, integrating with banking services improves functionality and personalized financial advice.